Faktor-faktor yang Mempengaruhi Kinerja Pemasaran dalam Usaha Budidaya Hidroponik di Tunas Hidroponik Menggunakan Regresi Linear - Supan Sopyan; Ratih Anggoro Wilis; Joko Suhariyanto (MAMEN: Jurnal Manajemen, 2024)
The cultivation of plants through hydroponics represents a novel innovation in the field of agriculture, especially in limited land areas. Hydroponics has the potential to yield agricultural products that are highly profitable. Additionally, each hydroponically grown product possesses specific competitive advantages that are assumed to enhance marketing performance. This research aims to explore the influence of product innovation and competitive advantages on marketing performance within hydroponic farming groups. The research methodology involves quantitative descriptive analysis, utilizing both t-tests and simultaneous F-tests to determine the impact of each variable and whether both variables collectively affect marketing performance. The variables examined include product innovation (X1) and competitive advantage (X2) as independent variables, and marketing performance (Y) as the dependent variable. The research findings demonstrate that both product innovation and competitive advantage individually have a significant impact on enhancing the marketing performance of hydroponic products. Moreover, both product innovation and competitive advantage, when considered simultaneously, significantly contribute to the improvement of marketing performance for hydroponically produced goods. This study underscores the importance of innovative hydroponic products possessing competitive advantages over other agricultural products. Such attributes are crucial for boosting marketing performance and indirectly creating consumer appeal for hydroponic products.